Three stages of the future physics researchers training at V. N. Karazin KhNU – SCPT laboratory - Kazachkova, N (Журнал физики и инженерии поверхности, 2016)
The work is dedicated to the good practice examples in the process of preparation of the future students for the departments of Physics. It have been supposed the three stages of the secondary school students’ experimental skills development. To teach students how to make simple research the extracurricular courses have been organised at the V. N. Karazin KhNU — SCPT Laboratory which is situated at the Department of Physics and Technology at the premises of V. N. Karazin Kharkiv National University. During such training students gain special profound knowledge of physics and seriously improve their experimental skills by doing self-made experimental projects using recycled materials, simple household objects, ordinary toys by means of real tools. Работа посвящена удачному опыту в привлечении и подготовке школьников к поступлению на физические факультеты ВУЗов Украины. Выделяются три этапа развития и формирования экспериментальных умений школьников. Для дополнительного обучения детей сотрудники физико- технического факультета ХНУ имени В. Н. Каразина и НФТЦ создали специальную лабораторию интерактивных методов обучения. Во время занятий учащиеся школ Харькова и области получают дополнительную подготовку по физике, серьезно повышают свои экспериментальные навыки, знакомясь с научным исследовательским оборудованием. Школьники делают свои первые исследовательские проекты, используя предметы домашнего обихода, обыкновенные игрушки, а также отходы производства и ненужные части недорого оборудования. Робота присвячена вдалого досвіду в залученні і підготовці школярів до вступу на фізичні факультети ВНЗ України. Виділяються три етапи розвитку та формування експериментальних умінь школярів. Для додаткового навчання дітей співробітники фізико-технічного факультету ХНУ імені В. Н. Каразіна та НФТЦ створили спеціальну лабораторію інтерактивних методів навчання. Під час занять учні шкіл Харкова і області отримують додаткову підготовку з фізики, серйозно підвищують свої експериментальні навички, знайомлячись з науковим дослідницьким обладнанням. Школярі роблять свої перші дослідні проекти, використовуючи предмети домашнього вжитку, звичайні іграшки, а також відходи виробництва і непотрібні частини недорого обладнання.